2018
DOI: 10.1038/s41467-018-03728-5
|View full text |Cite|
|
Sign up to set email alerts
|

The ASIC3/P2X3 cognate receptor is a pain-relevant and ligand-gated cationic channel

Abstract: Two subclasses of acid-sensing ion channels (ASIC3) and of ATP-sensitive P2X receptors (P2X3Rs) show a partially overlapping expression in sensory neurons. Here we report that both recombinant and native receptors interact with each other in multiple ways. Current measurements with the patch-clamp technique prove that ASIC3 stimulation strongly inhibits the P2X3R current partly by a Ca2+-dependent mechanism. The proton-binding site is critical for this effect and the two receptor channels appear to switch thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 57 publications
(71 reference statements)
2
42
0
Order By: Relevance
“…Because Cachd1 was able to coIP Ca V 2.2, partially co-localized with Ca V 2.2 on the cell surface of transfected cells, and also affected the reversal potential of these channels, it is clear that Cachd1 is not solely a trafficking protein but influences functional channels in the plasma membrane. The influence of another protein on the reversal potential of a channel, interpreted as an effect on its selectivity filter, has been observed previously ( Stephan et al., 2018 ). The lack of effect of Cachd1 on Ca V 2.1 currents may relate to a particular splice variant or be common to all isoforms of Ca V 2.1 and should allow us to localize the site of selective interaction of Cachd1 with Ca V 2.2 in the future.…”
Section: Discussionsupporting
confidence: 57%
“…Because Cachd1 was able to coIP Ca V 2.2, partially co-localized with Ca V 2.2 on the cell surface of transfected cells, and also affected the reversal potential of these channels, it is clear that Cachd1 is not solely a trafficking protein but influences functional channels in the plasma membrane. The influence of another protein on the reversal potential of a channel, interpreted as an effect on its selectivity filter, has been observed previously ( Stephan et al., 2018 ). The lack of effect of Cachd1 on Ca V 2.1 currents may relate to a particular splice variant or be common to all isoforms of Ca V 2.1 and should allow us to localize the site of selective interaction of Cachd1 with Ca V 2.2 in the future.…”
Section: Discussionsupporting
confidence: 57%
“…The effects reported include a decrease in the upregulation of purinoceptor 3 (P2X3) receptor and TNF-α protein, and a reduction of the phosphorylation and activation of extracellular signal-regulated protein kinases 1 and 2 (ERK1/2). A reduction in the activity of these proteins result in a decline in diabetic neuropathic pain since P2X3 is involved in acute, inflammatory, neuropathic, visceral and cancer pain; TNF-α plays a role in the peripheral mediation of neuropathic pain; and ERK (which are activated in spinal glial cells and lead to the synthesis of proinflammatory/pronociceptive mediators) can enhance and prolong pain [115][116][117]. There are other studies, however, for which different roles have been reported for ERK1/2.…”
Section: Anthraquinonementioning
confidence: 99%
“…As we provide evidence that spermidine permeates through the open pore of P2X receptors (Figure 2C ), we propose that P2X receptors may represent an alternative polyamine pathway that is under the control of ATP. Given the importance of spermidine for the function of several other ion channels, as well as the known interactions of P2X receptors with such channels (Khakh et al, 2005 ; Stanchev et al, 2009 ; Pougnet et al, 2014 ; Boué-Grabot and Pankratov, 2017 ; Stephan et al, 2018 ), the question is now raised as to what extent can P2X receptors be the physiological mediator of spermidine transit.…”
Section: New Directions Concerning the P2x Permeation Of Large Cationmentioning
confidence: 99%